Gastrointestinal illness among attendees of the FIFA Football World Cup 2022 in Qatar - Shams, Sherin (2025)
ObjectivesMass gathering events may facilitate the transmission of foodborne diseases. We determined the presentations and causative organisms of gastrointestinal illness among the attendees of the Fédération Internationale de Football Association Football World Cup 2022 (FIFA 2022). MethodsThe study was conducted at Hamad Medical Corporation in Qatar, which served as the national reference laboratory for all microbiology testing. We retrieved all stool testing data from the attendees of FIFA 2022 from October 1 to December 31, 2022. Stool microscopy for ova and parasite and cultures were performed on all samples. Polymerase chain reaction testing was performed for cases of suspected foodborne outbreaks or when a rapid result was required for public health response. ResultsAmong 2179 samples tested, one or more organisms were identified in 424 cases. The most common reasons for testing were acute diarrhea/gastroenteritis (51.4%), abdominal pain (11.5%), screening/surveillance of contacts (10.6%), and fever (7.6%). Bacteria were identified in 92.5% (Salmonella spp. 40%, Escherichia coli 25.7%, and Shigella spp. 8.8%), viruses in 7.8%, and parasites in 2.8% of the samples. ConclusionsThe number of individuals who underwent stool testing during the FIFA 2022 was low. The yield of stool testing was higher for those with acute diarrhea/gastroenteritis and fever but not for those with abdominal pain or for surveillance/screening.